Studi Kasus: Pengaruh Sertifikasi Authorized Economic Operator terhadap Kinerja Ekspor Pulp dan Kertas Indonesia - Irfan Ikhsanul; Dewi (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
This study aims to analyze the effect of the AEO program on the export performance of companies in Indonesia using the Difference-in-Differences method on panel data for the 2019–2023 period. The results of the analysis show that participation in the AEO program significantly increases the export value of companies, with a coefficient of 10.81 at a 1% significance level. In addition, regional inflation was found to have a negative impact on exports. These findings confirm the effectiveness of the AEO program in promoting international trade, particularly in the pulp and paper sector. However, this program has not optimally reached MSMEs. Therefore, expanding the scope of AEO and strengthening support for MSMEs are the main recommendations of this study.